Explaining the effective factors in sustainable urban development management, with emphasis on flourishing cities around metropolises (Case study: Lavasan city) - Hossein Sedaghat Nouri; Mohammad reza pourjahfar; Nader Zali (تحقیقات کاربردی علوم جغرافیایی)
This study examines the criteria for sustainable urban development management in thriving cities around metropolises. Based on the content analysis method in examining the theories in this field, a special conceptual model has been developed that presents the role of various indicators affecting the management of sustainable urban development in thriving cities. Also, based on the case study method, the city of Lavasan was selected as a case study to provide a realistic understanding of the role of various components on sustainable urban management in thriving cities around metropolises. The research method was based on quantitative and qualitative methods. Based on the field visit, initial discussions and conceptual model of purposeful questionnaires were prepared. SPSS21 and Smart-PLS statistical techniques were used to find the relationships of the variables and to analyze the information of the questionnaires. 376 questionnaires have been analyzed in relation to the components of sustainable urban development management. The results of the analysis show that the components affecting the management of sustainable urban development in Lavasan can be in physical-spatial dimensions, quality of life, intelligent management, justice and examined equality, governance, and optimal legislation. The results also show that the physical-spatial factor is the most important effective criterion. Also, the path of factor analysis shows that achieving urban prosperity in cities around metropolises begins with smart urban management, governance and appropriate legislation in the field of physical infrastructure. Space and quality of life infrastructure lead to the spread of justice and equality in the city and ultimately lead to urban prosperity.